Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Kelas V SD - Septi Susanti; Jayanti Jayanti*; Arief Kuswidyanarko (Universitas Negeri Makassar, 2022)
The research conducted by this researcher aims to determine (1) whether q is a significant influence on the learning outcomes of fifth grade students at SD Negeri 2 Pemulutan who are taught using the Discovery Learning model (2) Improve student learning outcomes in Mathematics subjects for addition and subtraction of fractions. in fifth grade students of SD Negeri 2 Pemulutan. This study uses an experimental method, namely True Experimental Design by using the form of the Pretest-posttest Control Group Design test. The test consists of 10 questions in the form of a description. The sample in this study consisted of two classes, namely the experimental class with 22 students and the control class with 20 students. The results of the hypothesis test obtained that the value of tcount is 3.569 while ttable is 2.021 so that Ho is rejected and Ha is accepted, it can be concluded that the Discovery Learning learning model has a significant effect on learning outcomes in mathematics, adding and subtracting fractions in class V SD Negeri 2 Pemulutan.